A Base‐Free Neutral Phase‐Transfer Reaction System. Issue 6 (15th April 2014) - Shirakawa, Seiji; Wang, Lijia; He, Rongjun; Arimitsu, Satoru; Maruoka, Keiji
Abstract Although phase‐transfer reactions catalyzed by using quaternary ammonium salts are generally believed to require base additives, we discovered that, even without any base additives, conjugate additions of 3‐substituted oxindoles to nitroolefins proceeded smoothly in the presence of lipophilic quaternary ammonium bromide under water–organic biphasic conditions. The mechanism of this novel base‐free neutral phase‐transfer reaction system is investigated and the assumed catalytic cycle is presented together with interesting effects of water and lipophilicity of the phase‐transfer catalyst. The base‐free neutral phase‐transfer reaction system can be applied to highly enantioselective conjugate addition and aldol reactions under the influence of chiral bifunctional ammonium bromides as key catalysts. The structure of the chiral ammonium enolate intermediate is discussed based on the single‐crystal X‐ray structures of relevant ammonium salts and the importance of bifunctional design of catalyst is clearly explained in the model of intermediate.